EVALUASI SEDIAAN SABUN CAIR ANTISEPTIK EKSTRAK ETANOL LIDAH MERTUA (Sansevieriae trifasciata Prain) - Deri Islami; Tika Anggraini (LPPM Universitas Abdurrab, 2023)
Tongue-in-law (Sansevieria trifasciata Plain) is a plant originating from the African continent. This plant is known as an antiseptic. The compounds contained in the tongue-in-law plant that have a role as antiseptics are flavonoids, phenols, and saponins because the active substance compounds contained in the ethanol extract of tongue-in-law can inhibit bacterial growth. This study aims to evaluate the preparation of liquid soap of ethanol extract of tongue-in-law with a concentration of 1%, 3%, and 5%. The method used in this research is a laboratory experiment regarding the evaluation of liquid soap preparations including organoleptic testing, pH, foam height, specific gravity, and free alkali. The test results of liquid soap preparations are determined by the quality requirements of SNI 06-4085-1996. The observation results of pH testing obtained F0 and F1 values did not meet the quality requirements of SNI 06-4085-1996, while F2 and F3 met the quality requirements of SNI 06-4085-1996. Specific gravity test on samples F0, F1, F2, and F3 did not meet the requirements of SNI 06-4085-1996. While the foam height test on F0, F1, F2, and F3 meets the quality requirements of SNI 06-4085-1996. Free alkali testing on liquid soap obtained values of F0, F1, F2, and F3 did not meet the quality requirements of SNI 06-4085-1996.